EFFORTS TO CONTROL THE RISK OF UNSAFE CONDITION AND UNSAFE ACTION IN MEDICAL EQUIPMENT REPAIR WORKERS AT HAJJ GENERAL HOSPITAL, MEDAN - Ahmad Syukroni Sinaga; Risna Risna; Jannah Widya Sari Limbong; Shahrani Dwianti Pane; Laila Najmi; Putra Apriadi Siregar (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2022)
Medical device repair workers have a potential risk of work accidents due to unsafe actions and unsafe conditions when repairing medical devices which can endanger and eliminate their work. The purpose of this study is to know unsafe actions and unsafe conditions for medical technicians and efforts to control the risk of harm due to unsafe conditions and unsafe conditions. This study uses a qualitative method with an observational approach using loss studies. This research was conducted for 1 month at the Medan Hajj General Hospital in the Social Sciences Room of the Hospital from January 16 to February 16 2023. Data collection was through secondary data and interviews. Sampling in research with Purposive Sampling. The number of samples was 4 informants, namely the main informants, and 3 informants (medical device technicians). Workers work in standard time, namely 8 hours/day with 1 hour break. In the work environment, informants stated that the work environment was very good and friendly, mutually supportive. In the workplace, cleaning, cleaning and tagging are reduced, so that the workplace is potentially hazardous to workers. The behavior of workers in carrying out their work, the SOP of workers has carried out well, but the use of PPE workers has not implemented it, and resulted in workers being stabbed by tool bolts, electrocuted, and burned while doing work which if allowed to continue will be fatal which will harm workers and hospital. Keywords: Unsafe Action ;Unsafe Condition; Potential Risk; Work Accidents.